2006
DOI: 10.1097/01.acm.0000236516.63055.8b
|View full text |Cite
|
Sign up to set email alerts
|

Are Discharge Summaries Teachable? The Effects of a Discharge Summary Curriculum on the Quality of Discharge Summaries in an Internal Medicine Residency Program

Abstract: Interns who received instruction on discharge summary skills improved the quality and of their discharge summaries. Adding feedback to the curriculum provided more benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 10 publications
1
56
0
1
Order By: Relevance
“…[22][23][24] This poor documentation may reflect a lack of appreciation for the needs of the sub-acute care patient and multi-disciplinary care team, the need for a standardized approach to discharge documentation, and the absence of regulation and assessment to ensure discharge documentation quality. 1,6,16 Additional research is needed to better understand the connection between discharge documentation quality and patient/system outcomes. We found both explicable and modifiable predictors of poor documentation for actionable components, especially the timing of discharge summary creation in relation to discharge and the author's training level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24] This poor documentation may reflect a lack of appreciation for the needs of the sub-acute care patient and multi-disciplinary care team, the need for a standardized approach to discharge documentation, and the absence of regulation and assessment to ensure discharge documentation quality. 1,6,16 Additional research is needed to better understand the connection between discharge documentation quality and patient/system outcomes. We found both explicable and modifiable predictors of poor documentation for actionable components, especially the timing of discharge summary creation in relation to discharge and the author's training level.…”
Section: Discussionmentioning
confidence: 99%
“…16 Trainees are usually informally instructed during residency using a wide variety of clinical-work processes. This ad-hoc approach may reflect a lack of evidence-based discharge summary recommendations and poor awareness of the importance of post-hospital transitions.…”
Section: Introductionmentioning
confidence: 99%
“…Deficiencies in the content, template or delivery of discharge summaries contribute to poor quality of care, poor follow-up, adverse events and medical error [4][5][6][7] . Interventions to improve the quality of discharge summaries have focused on the modernization of the production of the summaries 8 , standardization of content through didactic interventions 9 , templating or providing more explicit guidelines for use by residents 10 . Each of these can be at least partially successful 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite widespread awareness of the negative consequences of poor communication in handoffs and transitions of care, little research has identified best practices. 7,48,49 Authors such as Hilligoss and Cohen 50 and Horowitz and colleagues 51 suggest that education for effective handoffs incorporate direct observation and feedback or handoff behaviors, use of reflective practice as a way to inculcate vigilance, and attention to differences in handoff types (for example, within-unit handoffs [between trainees who are largely known to one another] and betweenunit transfers of care [between trainees or attending physicians who are strangers to one another]). We are developing a handover tool for residents and attending physicians 7 have reviewed the literature on handoffs in a number of high reliability industries and concluded that faceto-face handoffs have the highest accuracy and reliability.…”
Section: Discussionmentioning
confidence: 99%